Protective effect of Erythrina senegalensis sequential extracts against oxidative stress in SC-1 fibroblasts and THP-1 macrophages - Ewura S. Yahaya; Werner Cordier; Paul A. Steenkamp; Vanessa Steenkamp (GarVal Editorial Ltda., 2020)
Context: Erythrina senegalensis (ES) DC. is used traditionally in the management of various free radical-related diseases, including wound healing. Aims: To evaluate sequentially prepared leaf extracts of ES for the ability to protect against oxidative stress in fibroblasts and macrophages. Methods: Sequential extracts were prepared using hexane, ethyl acetate, methanol and water in increasing polarity. Chemical profiling was done with ultra-performance liquid chromatography coupled with mass spectrometry (UPLC-MS). Cytotoxic potential was determined using the sulforhodamine B staining assay, phase contrast, PlasDIC, and live/dead staining microscopy. The ability to scavenge the ABTS and DPPH free radicals was assessed, while the effect on AAPH-induced oxidative stress was evaluated by measuring reactive oxygen species (ROS) release. Results: A previously reported compound (neobavaisoflavone), and three others (kaempferol, rutin, and rotenone) were tentatively detected. With regards to cytotoxicity, no IC50 could be determined up to the highest concentration tested (100 µg/mL) in both THP-1 and SC-1 cells. The methanol extract displayed the greatest antioxidant activity against the free radicals (IC50 = 44.86 µg/mL [ABTS]; 291.1 µg/mL [DPPH]) and AAPH-induced intracellular ROS in macrophages (1.0-fold reduction at 100 µg/mL). The protective effect of the extracts (1 - 100 µg/mL) was comparable to the positive control (Trolox), which decreased ROS by 1.30-fold at 5 µg/mL. Conclusions: A significant ability to protect against oxidative stress was exhibited by extracts from ES, with no observed cytotoxicity. Secondary metabolites from the plant may have potential for use as alternative medicines in ROS-induced diseases such as chronic wounds.